2022
DOI: 10.1039/d2dt02603a
|View full text |Cite
|
Sign up to set email alerts
|

Hierarchically structured nickel/molybdenum nitride heterojunctions as superior bifunctional electrodes for overall water splitting

Abstract: Transition metal nitrides are considered to be one of the most promising metallic materials for electrocatalytic water splitting. However, the low density of active sites and weak reaction kinetics still...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 41 publications
1
2
0
Order By: Relevance
“…The performance is superior to some of the recently reported MoO 2 and NiMoN catalysts. 9,15,17,18,[28][29][30][31] The larger oxidation peak at an overpotential of B0.2 V (Fig. 2a) compared with other catalysts can be attributed to the formation of Ni 0 phase in the Ni 0.2 Mo 0.8 N phase, which is very susceptible to oxidation during the OER, and similar results have been observed in other Ni 0.2 Mo 0.8 N-based OER catalysts.…”
supporting
confidence: 79%
“…The performance is superior to some of the recently reported MoO 2 and NiMoN catalysts. 9,15,17,18,[28][29][30][31] The larger oxidation peak at an overpotential of B0.2 V (Fig. 2a) compared with other catalysts can be attributed to the formation of Ni 0 phase in the Ni 0.2 Mo 0.8 N phase, which is very susceptible to oxidation during the OER, and similar results have been observed in other Ni 0.2 Mo 0.8 N-based OER catalysts.…”
supporting
confidence: 79%
“…The low Tafel slope suggests fast HER kinetics progress on NMN/NF following the Volmer-Heyrovsky mechanism. 47,48 The electrochemical impedance spectra (EIS) of all samples were collected at a potential of −0.220 V. As shown in Fig. 3d, the charge transfer resistance (R ct ) of NMN/NF (0.7 U) is obviously lower than that of Pt/C (1.8 U), Ni 4 Mo/NF (2.1 U) and NMO/NF (14.6 U), indicating its most efficient charge transfer ability to catalyse the HER among all catalysts.…”
Section: Her Performance Of Nmn/nfmentioning
confidence: 99%
“…[3][4][5] A simple method to enhance the electrochemical performance and cycling stability of single-phase Mo 5 N 6 is to modify the electronic structure by hybridizing with other active components and/or by introdu-cing another metal element. 6 Presently, it has been reported that molybdenum oxide (MoO 3 ) possessing a reversible surface oxygen ion exchange capacity is an active material in electrocatalytic systems, which could promote the charge transfer and the generation of O* during the OER process. 7,8 Moreover, many studies demonstrated that the presence of Fe can enhance the OER activity of metal centers by modulating their local electronic structure.…”
Section: Introductionmentioning
confidence: 99%